Busca ativa: uma abordagem para a análise da demanda em programas corporativos de ergonomia - Tonin, Luiz Antonio (2014)
This study discusses the stage of demand assessment of a corporate ergonomic program from a big company in the mechanical metal sector of high aggregated value. The topics covered in this work present the approach, methodological grounds and tools used in the Active Search for ergonomics issues. This Active Search is a systematic approach for mapping ergonomic demands developed and applied in the case presented. This approach encompasses a procedure and software which will be presented in this work. The Active Search begins after the analysis of medical related absenteeism data. They indicate the sectors where there may be critical situations in which ergonomic intervention is needed. After that, the required tasks are identified for each sector. Those tasks are analyzed by workers who, individually, indicate the ones that are critical and, among these, they also study their level of criticality in a preestablished scale. Finally, the data are compiled and submitted to the validation and prioritization of workers. The process is a collective activity which involves all the workers of the sector and the supervisors. Later, the selected activities are sent for the ergonomic situation analysis. This is an action research grounded study. The results of this work have shown a method which helps the identification of the tasks considered critical by the workers and that helps in the synthesis of the collected data. The relations among demands for family and products; ergonomic demands from technology used in manufacturing; the production sector and its respective directors and single manufacturing units are presented in the moment of synthesis. In the view of the results for such synthesis, it is possible to identify the distribution in the company of the ergonomic demands, according to these categories. This can aid the organization to decide the strategies to reduce critical work situation and to determine the systematically operations of the action analysis as well as the ergonomic improvements for the project. In addition, other results of this study are presented as an approach in the analysis phase in the ergonomic demand, as an operant model and as a technological innovation.